Fragmentation model for large L/D (Length over Diameter) explosive fragmentation warheads - Vladimir M. Gold (Defence Technology, 2017)
New advanced numerical computer model enabling accurate simulation of fragmentation parameters of large Length over Diameter (L/D) explosively driven metal shells has been developed and validated. The newly developed large L/D multi-region model links three-dimensional axisymmetric high strain high strain-rate hydrocode analyses with the conventional set of Picatinny Arsenal FRAGmentation (PAFRAG) simulation routines. The standard PAFRAG modeling technique is based on the Mott's theory of break-up of idealized cylindrical “ring-bombs”, in which the length of the average fragment is a function of the radius and velocity of the shell at the moment of break-up, and the mechanical properties of the metal. In the newly developed multi-region model, each of the shell region, the break-up is assumed to occur instantaneously, whereas the entire shell is modeled to fragment at multiple times, according to the number of the regions considered. According to PAFRAG methodology, the required input for both the natural and the controlled fragmentation models including the geometry and the velocity of the shell at moment of break-up had been provided from the hydrocode analyses and validated with available experimental data. The newly developed large L/D multi-region PAFRAG model has been shown to accurately reproduce available experimental fragmentation data.